Pengentasan Kemiskinan Berbasis Jasa Ekosistem - Zairin Zairin (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2017)
Poverty is a matter of concern to the world, especially in developing countries like Indonesia. This is evidenced by the adoption of the Millennium Development Goals (MDGs) by the United Nations, which is one of its objectives is to eradicate poverty and hunger. There are many things that governments can do about reducing poverty, because the government basically has the ability to access and manage natural resources, such as forests. Providing compensation for environmental services in the form of land management rights to poor farmers is believed to be able to reduce poverty and income distribution. In addition, other forms of increasing public incomes can also be made by strengthening roles in managing natural resources sustainably. Government policies to support the development of "Payments for environmental services" mechanisms and "Collaborative Management" mechanisms are essential to realize the benefits of conservation areas for the surrounding communities. In collaborative management mechanisms, local communities and all stakeholders collaborate and share roles in managing each conservation area. So that the water catchment area for the water supply of PDAM or bottled water can be fulfilled and they have to pay for the services of nature and forest farming efforts in the catchment area of ​​the source water.